SUID-AFRIKA EN NEDERLAND - VREEMDELINGE VIR MEKAAR.: DIE JARE NA 1960 (Historia, 2021)
South Africa and the Netherlands - strangers to each other. The years from 1960 The relationship between two related nations can very often be emotionally charged. The Dutch and the Afrikaners always had a love-hate relationship. They harboured divergent expectations of one another on grounds of ties of kinship. As a result of the Second World War the Dutch abhorred anything associated with racialism or racial discrimination. For that reason apartheid was fundamentally and on principle, unacceptable to them. After Sharpeville the opinion was widely held in the Netherlands that the apartheid policy could no longer be regarded as an internal affair, because it violated basic human rights and threatened world peace. The sixties were characterised by a cultural revolution and diverse political protest movements in the Netherlands. The Dutch developed an international outlook; in contrast the Afrikaner sought his salvation in nationalism and isolation. The holier than thou attitude of the Dutch as regards foreign policy estranged them even further from the Afrikaners. Leading figures of the Anti-Revolutionary Party (a Christian Protestant party) developed a feeling of solidarity with the weak and the oppressed throughout the world. Conceptual and psychological aspects of language usage, which can give rise to misunderstanding, also accentuated the process of estrangement. Die verhouding tussen twee stamverwante volke kan heel dikwels erg emosioneel verloop. Nederlanders en Afrikaners het nog altyd 'n spesiale haat-liefde verhouding met mekaar gehad. Die twee stamlande het op grond van die historiese bande van stamverwantskap uiteenlopende verwagtinge van mekaar gekoester. Die Tweede Wêreldoorlog het tot gevolg gehad dat die Nederlanders 'n intense weersin ontwikkel het in alles wat verband hou met rassisme of rassediskriminasie. Daarom was apartheid fundamenteel en prinsipieel onaanvaarbaar vir die Nederlangers. Na die gebeure by Sharpeville is die mening wyd in Nederland gehuldig dat die apartheidsbeleid nie langer as 'n binnelandse aangeleentheid beskou kon word nie, omdat dit die basiese menseregte skend en selfs die wêreldvrede bedreig. Die jare sestig in Nederland is gekenmerk deur 'n kulturele revolusie en diverse politieke protesbewegings. Die Nederlanders het 'n internasionalistiese lewensuitkyk ontwikkel; daarenteen het die Afrikaner se krag in nasionalisme en isolasie gelê. Die morele sendingsdrang van Nederland ten opsigte van buitelandse beleidsake het hom verder die gramskap van die Afrikaner op die hals gehaal. Leiersfigure van die Anti-Revolutionaire Partij ('n Christelik-Protestantse party) het 'n wêreldwye solidariteit ontwikkel met die swakkes en verdruktes. Die taalverskil tussen Nederlands en Afrikaans, wat tot misverstande aanleiding kan gee, het die vervreemdingsproses verder geaksentueer.
Keywords: Suid-Afrika; Nederland; South Africa; Netherlands; 1960; Dutch; Afrikaners; Nederlanders; cultural revolution; apartheid; Sharpeville; kulturele revolusie; political protest; foreign policy; buitelandse beleidsake; history; geskiedenis; historia; politieke protes